Towards Sustainable Construction Developing a Framework for Identifying Ecosystem Services and Biodiversity Indicators in Compliance with CSRD - Josefsson, Amanda; Klintberg, Matilda (My University, 2024)
With global population growth and increasing urbanisation, it is important to monitor and mitigate the impacts of land-use change on ecosystems and biodiversity. In order to foster a culture of accountability among companies, the EU has introduced the Corporate Sustainability Reporting Directive (CSRD), aimed at expanding the scope of sustainability reporting to include more companies. The aim is also to enhance the comparability, trustworthiness, and inclusion of relevant data in sustainability reporting. There are 13 Reporting standards within CSRD called European Sustainability Reporting Standards (ESRS), and the focus here is ESRS E4 which covers biodiversity and ecosystems. The aim of this master’s thesis is to investigate how the construction and building company Derome can measure ecosystem services and biodiversity, and use the results to report this in line with CSRD. This master’s thesis is done in collaboration with Derome which is a company situated in the south-west of Sweden. From the fiscal year of 2025, Derome is obligated to report according to CSRD and ESRS E4, which means that Derome need to develop methodologies for measuring and monitoring their impact on biodiversity and ecosystems. A literature study and a semi-structured interview study with employees at Derome were conducted to achieve this. The results of this master’s thesis shows that indicators, for ecosystem services and biodiversity can be identified using the combined framework, DPSIR-E. This framework, built upon the DPSIR (Drivers, Pressures, State, Impact, Response) model, incorporates three additional steps to ensure the development of suitable indicators: one dedicated to the actors engaged in indicator development, another focused on defining the purpose of the indicators, and a third dedicated to establishing evaluation criteria, resulting in the additional “-E” to the combined framework. The efficacy of this combined framework was demonstrated through its application to two of Derome’s construction sites, resulting in the identification of 22 indicators measuring ecosystem services and biodiversity at Göinge by and Göingegården, including example values for Göinge by. Lastly, the importance of sector-specific disclosure requirements for the construction and building sector were identified. Further, common monitoring data points or indicators is needed to ensure comparable results regarding companies impacts on ecosystems and biodiversity within the sector.
Keywords: Ecosystem services; biodiversity; CSRD; ESRS E4; ecosystems; DPSIR; indicators; construction site